(untitled) (Al-Qamar, 2021)
Polygamy refers to a marriage involving more than two partners. Polygamy is a social practice that is not widely accepted in most nations and is prohibited by law. Usually, this phrase would refer to a sort of marriage in which there have been more than one spouse, but at the same time, this will apply to more than one wife. For a long time, many communities, tribes, and civilizations around the world viewed polygamy as a regular practice, and there were no issues with a man having more than one wife, and sometimes even a woman having more than one husband. This research investigates the framework of polygamy in Islam and international human rights law, focusing on Pakistan. The application of Islamic law in relation to polygamy is compared with the needs and challenges of legal dynamism in terms of suitability with people, place, and time in the light of international human law and domestic legal framework. The study is divided into three sections: 1. polygamy in Islam; 2. Modern Human Rights Law where polygamy is prohibited; and 3. Pakistani legislation where polygamy is permitted within a regulated framework.